2018
DOI: 10.1519/jsc.0000000000001835
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Ballistic and Nonballistic Bench Press on Mechanical Variables

Abstract: Moir, GL, Munford, SN, Moroski, LL, Davis, SE. The effects of ballistic and nonballistic bench press on mechanical variables. J Strength Cond Res 32(12): 3333-3339, 2018-The purpose of this study was to investigate the effects of ballistic and nonballistic bench press performed with loads equivalent to 30 and 90% 1 repetition maximum (1RM) on mechanical variables. Eleven resistance-trained men (age: 23.0 ± 1.4 years; mass: 98.4 ± 14.4 kg) attended 4 testing sessions where they performed one of the following se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Particularly when working with older adults, it should be considered that power-oriented RT (i.e., performed at maximal velocity) may yield greater improvements in muscle function and functional ability than traditional RT (6,8), irrespective of the magnitude of the loads being used (from 20 to 85% of 1repetition maximum [1RM]) (14,32). Power-oriented RT increases the neuromuscular system demands (33) and mechanical output registered during training (27). In young people, poweroriented RT sessions using different loading schemes (i.e., heavy, moderate, and light) have been shown to evoke different acute neuromuscular and hormonal responses (25).…”
Section: Introductionmentioning
confidence: 99%
“…Particularly when working with older adults, it should be considered that power-oriented RT (i.e., performed at maximal velocity) may yield greater improvements in muscle function and functional ability than traditional RT (6,8), irrespective of the magnitude of the loads being used (from 20 to 85% of 1repetition maximum [1RM]) (14,32). Power-oriented RT increases the neuromuscular system demands (33) and mechanical output registered during training (27). In young people, poweroriented RT sessions using different loading schemes (i.e., heavy, moderate, and light) have been shown to evoke different acute neuromuscular and hormonal responses (25).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, heavier loads result in reduced velocity, ultimately negating the benefits of these exercises by preventing the effective projection of the load into the air. In this vein, prior studies (Sanchez-Medina et al, 2009;Moir et al, 2018;Loturco et al, 2020) have shown that when male athletes lift loads surpassing approximately 75%-80% Frontiers in Physiology frontiersin.org of their 1RM, they are unable to harness the benefits of the ballistic bench press. This is because, at these specified loads, the concentric phase of the exercise primarily becomes propulsive, preventing athletes from effectively launching the loaded barbell into the air.…”
Section: Discussionmentioning
confidence: 99%
“…Non-balllistic lifts are traditional strength training lifts, like the back squat and the bench press, performed with low to moderate loads and lifted at maximal velocity The effect of HVPT on RHIE and RPA 5 This is a post-peer-review, pre-copyedit version of an article published in Sports Medicine. The final authenticated version is available online at: http://dx.doi.org/10.1007/s40279-020-01273-0 (14). In ballistic lifts the system mass (the lifter and the load) or the object (for example a barbell) are projected into flight, as in a squat jump and bench throws respectively (14).…”
Section: Training For Repeated High Intensity Effortsmentioning
confidence: 99%
“…The final authenticated version is available online at: http://dx.doi.org/10.1007/s40279-020-01273-0 (14). In ballistic lifts the system mass (the lifter and the load) or the object (for example a barbell) are projected into flight, as in a squat jump and bench throws respectively (14). The weightlifting exercises, the clean, the snatch, the jerk, and their derivatives are also used in traditional power training (12,15).…”
Section: Training For Repeated High Intensity Effortsmentioning
confidence: 99%